Determinants of Hypertension in Seribu Utara Island District, Seribu Islands - Malau, Herland A.; Simanjuntak, Natanael Martua Parningotan; Triono, Purwa Septa Dupit (Cities and Urban Development Journal, 2023)
Background: Hypertension is a public health problem, including in the Seribu Islands. This region has unique characteristics, such as limited access to health facilities and a lifestyle that is different from urban areas in general. Genetic factors, age and obesity can affect the prevalence rate of hypertension in Seribu Utara Island District. Aims: This research was conducted to help develop an effective hypertension prevention program in Seribu Utara Island District. Methods: descriptive analytic with a cross-sectional study approach based on socio-demographic conditions, family history of hypertension, Body Mass Index (BMI), and waist circumference. Data analysis was conducted using the chi-square method and multiple logistic regression. The subjects in this study were 100 individuals from the Seribu Utara Island District who were diagnosed with Non-Communicable Diseases (NCDs) such as Diabetes Mellitus and/or Hypertension, based on the data from the patient profile report of the internal medicine department at the Regional General Hospital (RSUD) of the Thousand Islands in the year 2021. Results: The research showed that genetic factors and age have a significant relationship with the prevalence of hypertension in the Seribu Utara Island District. Meanwhile, the determinants of BMI and waist circumference were found to be not significant in relation to the prevalence of hypertension in the Seribu Utara Island District. Conclusion: Family history of hypertension and age can be the focal points in efforts for prevention, early detection, and management of hypertension in the community.